Looks at what isn't there: eye movements on a blank screen when processing negation in a first and a second language - Vanek, Norbert; Matić Škorić, Ana; Košutar, Sara; Matějka, Štěpán; Stone, Kate (Frontiers in Human Neuroscience, 2024)
Is negation more difficult to process than affirmation? If it is, does processing negation in a second language (L2) compound the difficulty compared to the first language (L1)? This article addresses the issues of difficulties in processing different types of negation in the L1 and L2 by looking at the differences in the ways in which comprehenders anticipate upcoming visual information during sentence processing. Using a blank-screen paradigm, we recorded eye fixations of Croatian native speakers and Croatian learners of English while they were anticipating matching or mismatching pictures to sentences with various types of negation in L1 (Croatian) and L2 (English). Using a between-group design, we manipulated sentence polarity (affirmative vs negative), negation type (sentential vs negative quantifier) within both L1 Croatian and L2 English so that we could observe potential anticipation effects varying as a function of the two predictors. In line with previous studies, affirmation in the L1 was easier to process than negation, and participants were able to anticipate sentence-picture matches in both the L1 and the L2 group. In contrast with our prediction, anticipatory looks did not significantly vary across negation types in Croatian based on the number of structural cues. In L2 English, learners exhibited prediction ability across negation types. These findings go against the view that comprehension in L2 comes with a reduced ability to generate expectations, and they highlight the robustness of mental simulations in both L1 and L2 negation processing.